ETHICS OF POLITICS AND VALUES OF SOCIAL MEDIA: AN IDEAL USE. - Diou, Nadeem Ahmed; Shaheen, Rubina; Issani, Maria; Baloach, Abdul Hayee (The journal of contemporary issues in business and government, 2021)
Social media got unpredictable fast growth and now social media is used in all aspect of life. Social media has influenced all areas of life and politics. Government organization using social media to be in touch with their workers and communication of office work where as political parties are using social media for sharing party activities and manifesto among the volunteers and people. It is not only that even social media is very important tool to attract new workers towards party manifesto even social media is used as a propaganda tool across the world. In Modern democracy the politicians are using social media in very short period of time to engage their voters and citizens are into discussion and direct dialogue. Values of media are not appropriate followed by people. Political representative is engaged in creating social media a platform to be in connection with workers but people consider it as a platform to ventilate themselves and in struggle of to expose political representative. In this study, it is measured that Social Media and Media Ethics are associated to each other. For this Pearson correlation was used Demographic Statistic, And Regression Analysis were Applied to understand the reality eventhickness of data was tested through Cronbach’s alpha. This study concluded ethics of politics and values of media are associated but not properly understood by people.